INFORMATION SYSTEM OF GOODS SALES AND SUPPLY IN CV. TASMA JAYA BANDAR LAMPUNG - Hilda Dwi Yunita (IJISCS (International Journal of Information System and Computer Science), 2018)
Processing of disposal and supply goods data in CV. Tasma Jaya Bandar Lampung is used manual way and without computerized system, so it often caused mistaken in its disposal entry. Based on this case, technique for researched used were observation, interview, and refference study. Problem solving for that case through implementation the disposal, supply, report of disposal transaction information system. Based on the result, any new disposal and supply for revise the old system that has many deficiency.